In-situ synthesis of magnetic nanoparticle immobilized heterogeneous catalyst through mussel mimetic approach for the efficient removal of water pollutants - Das, Tushar Kanti; Ganguly, Sayan; Ghosh, Sabyasachi; Remanan, Sanjay; Ghosh, Suman Kumar; Das, Narayan Ch (Colloid and interface science communications, 2019)
Naturally occurring 2:1 layered phyllosilicate tactoids decorated by in situ synthesized magnetite nanoparticles via mussel inspired surface chemistry. Polydopamine has been exploited here to promote surface energy of the clay tactoids resulting in fast anchoring of magnetic nanoparticles (MNP) on to the phyllosilicate layers. Such a typical metal-organic framework based heterogeneous catalyst has immense interest in wastewater treatment. 4-nitrophenol and Congo red were selected here as model pollutants, which degraded to the aqueous environment in minimal real-time. Nonetheless, the catalyst fractions are easy to remove by magneto-gravimetric strategy and also recycled up to six times without deteriorating its catalytic features. [Display omitted] •Fabrication of heterogeneous catalytic magnetic nanoparticles (MNP) immobilized Monmorillonite (MMT) nanostructure.•Study the efficiency of catalyst for catalytic reduction of 4-nitrophenol (4-NP) as well as degradation of congo red (CR).•Significant loss in catalytic activity after recycling demonstrates strong interaction between polydopamine and MNP.•Synthesized nanocomposite shows high recyclability up to six numbers of cycles.